Harmonic reduction in a three-phase rectifier with sinusoidal input current - Younis M.A.A.; Rahim N.A.; Mekhilef S. (2023)
This article proposes a new approach to reduce harmonics generated by a three-phase diode rectifier. The proposed approach uses the input filters, six controllable switches, high-frequency isolation transformer, and the three-phase diode rectifier. The switching of the controllable switches is modulated by a novel pulse-width modulation (PWM) implemented in an XC4006 field programmable gate array (FPGA). This approach realizes sinusoidal input current waveforms with low electromagnetic interference and arbitrary output voltage. The output voltage can be controlled by variation of the modulation index in the range (0 ? M ? 0.98). The experimental results to compare performance between with and without the proposed approach are carried out to confirm its feasibility.